Entrapment of maltogenic amylase and cyclodextrin glucanotransferase for malto-oligosaccharides synthesis - Muhammad Firdaus Kumar, Nurhidayah Kumar (2022)
Starches in various forms are extensively utilized industrially for a variety of purposes. Malto-oligosaccharides (MOS) can be synthesized by maltogenic amylase (MAG1) from starch. However, using maltogenic amylase alone has significant drawbacks, including inadequate specificity for starch and low MOS yield. Cyclodextrin glucanotransferase (CGTase) can convert starch to cyclodextrins, the preferred substrates for MAG1. Employing the substrate diversity of MAG1 and CGTase, the use of both enzymes could provide a new synthesis pathway for MOS from a low-cost and widely available starch. Although free enzymes can be used to produce MOS, this method is hindered by low enzyme recovery and lack of enzyme stability, making it unsuitable for industrial applications. Enzyme immobilization strategy was used in this study to alleviate these disadvantages. Entrapment immobilization technique that uses calcium alginate (CA) beads were developed to improve the stability and reusability of free MAG1 and CGTase. Factors affecting the formation of the beads for both CA-MAG1 and CA-CGTase were investigated. These include sodium alginate concentration, calcium chloride concentration and enzyme loading. The highest activity recovery of CA-MAG1 was obtained with 75 U MAG1 loading, 2 % (w/v) sodium alginate, and 0.8 % calcium chloride that yielded 88.06 % of activity recovery. Meanwhile, the optimum conditions for CA-CGTase were achieved at 1000 U CGTase loading with 2.5 % (w/v) sodium alginate and 0.8 % calcium chloride exhibited 89.45 % activity recovery. CA-MAG1 retained 41 % of the initial activity after 60 min incubation at 45 °C compared to free MAG1 in which the activity dropped after 10 min of incubation. After incubation for an hour at 70 °C, CA-CGTase retained 44 % of its initial activity compared to 11 % of free CGTase. A kinetic study discovered that CA-MAG1 and CA-CGTase have shown a relatively high affinity towards starch, with Km value of 6.86 mM. Moreover, the developed beads revealed low enzyme leaching and were able to be reused up to 8 cycles with more than 50% of activity retention. Starch hydrolysis reactions were carried out by two-steps and one-pot methods. For the two-steps method, MOS yield of 183.82 mg/g was obtained when 3 U MAG1 loading, 10 U CGTase loading, 2 % (w/v) of starch, and a total reaction of 5 h. With a 2 h reaction time, MAG1 loading to CGTase loading in a 3 U: 7 U ratio, and 1.5 % (w/v) starch loading, the one-pot technique provided 190.48 mg/g of MOS, which was 0.97-fold more than the two-steps method. The entrapment method used to produce CA-MAG1 and CA-CGTase have proven to be a viable strategy for developing stable and reusable enzymes that are potentially useful biocatalysts for starch conversion in MOS production.